Designing a Crowdfunding Information System in Kota Pari Village using the Laravel Framework - Abdul Khaliq; Maya Syaula; Muhammad Muttaqin; Sahrial (Yayasan Sinergi Multidimensi Kreatif, 2024)
This research aims to design a crowdfunding information system to empower the community in Kota Pari Village in raising funds for various projects and initiatives. The system is built using the Laravel framework and is designed with a scalable and secure architecture, consisting of key components such as the user interface, project management system, donation management system, user management system, reporting system, database, and API. Key features implemented include user registration and profiles, project management, donations and payments, notifications, and analytics. The waterfall methodology is used in system development, including the stages of needs analysis, system design, implementation, testing, and deployment. The results of this research are in the form of a web-based crowdfunding information system design which is expected to increase access to funding, transparency, and community participation in village development. Leveraging the Laravel framework provides advantages in terms of development speed, security, and system scalability. This research contributes to the development of technological solutions for economic and social empowerment in rural areas.